Stakeholders' Reactions to ESG Scores and Political Connections: Evidence from Tobin's Q and Stock Performance - Puspitasari, Nindya Farah Dwi; Nikensari, Sri Indah; Pesi Suryani (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2025)
This study seeks to determine how environmental, social and governance (ESG) scores and corporate political connections jointly shape stakeholder reactions, captured through firm-level valuation (Tobin’s Q) and stock returns, among Indonesian listed companies. Using firm-level panel data for listed companies over 2020-2023, this quantitative study applies Generalized Least Squares estimation in Stata, and augments the analysis with contextual information drawn from peer-reviewed journals and reputable online sources. Stronger ESG scores raise firm valuations (Tobin’s Q) without enhancing total stock returns, whereas political connections lower Tobin’s Q by about 0.17 yet deliver an average excess return of roughly 0.69 percentage points. The evidence indicates that sustainability credentials and political affiliations influence performance in mutually reinforcing yet distinct ways: stronger ESG scores are associated with durable gains in enterprise value, whereas political connections translate into only short-lived share-price uplifts. Consequently, the findings encourage executives to invest in substantive ESG improvements as a foundation for lasting value creation, while cautioning regulators that the abnormal returns enjoyed by politically connected firms may stem from rent-seeking rather than genuine efficiency.